Direct inoculation of a biotrickling filter for hydrogenotrophic methanogenesis. (December 2020) - Dahl Jønson, Brian; Ujarak Sieborg, Mads; Tahir Ashraf, Muhammad; Yde, Lars; Shin, Juhee; Shin, Seung Gu; Mi Triolo, Jin
Graphical abstract: Abstract: Hydrogenotrophic biomethanation in a biotrickling filter has been reported to be a proven technology for biological biogas upgrading in recent studies. However, the preparation of enriched hydrogenotrophic methanogens in a separate reactor prior to biomethanation in a trickled bed is a lengthy procedure and therefore hard to apply on an industrial scale. This study explored the direct inoculation of anaerobic biogas digestate for simultaneous enrichment of hydrogenotrophic methanogens and biofilm immobilisation in a trickled bed system. The direct inoculation and formation of hydrogenotrophic biofilm was successful and resulted in a stable H2 loading rate of 11  N m H 2 3 m R - 3 d - 1, with the highest specific methane productivity recorded at 3.03  N m 3 m R - 3 d - 1 and a purity of 98% CH4 in thermophilic conditions. The DNA analysis confirmed that hydrogenotrophic methanogens dominated the archaeal consortia.